Solusi Persamaan Schrodinger dengan Menggunakan Metode Transformasi Diferensial - Muhammad Abdy; Hisyam Ihsan; Dhea Ayu Rossyana Dewi (Journal of Mathematics, Computations and Statistics, 2021)
This study discusses the solution of linear partial differential equations, namely Schrodinger equation. The solution of the equation is done by using the differential transformation method which is a semi-numerical-analytical method, it can be used to solve both ordinary differential equations and linear or nonlinear partial differential equations. Differential transformation method is a method uses the theory of rank expansion in the form of transformation to determine solutions. In this study, two initial values in the given Schrodinger equation were used. Solutions with both initial values given are obtained using the Maclaurin series expansion. Then, the solution is simulated using Maple18 software. As a result, the differential transformation method in this study is one method that is able to solve a solution to the Schrodinger equation.